Effect of calcium hydroxide and combinations of ledermix and calcium hydroxide on inflamed pulp in dog teeth - (:unkn) unknown (WILLIAMS & WILKINS, 1996)
The effects of Ledermix + calcium hydroxide (Ca(OH)(2)) or Ca(OH)(2) alone on inflamed pulp tissues of dogs were studied, Fifty-nine upper incisor teeth of 10 dogs were used, Class V cavities were prepared and filled with amalgam after placement of decayed dentin particles. After 7 days, the decayed dentin and alloy were removed, and the pulps of the teeth were exposed, Ledermix and Ca(OH)(2) mixtures or Ca(OH)(2) atone were applied to the cavities. At the end of 7, 30, and 90 days, the teeth were extracted and examined histopathologically. Inflammation was found to be more prevalent in the 7- and 30-day groups that were treated with the Ledermix + Ca(OH)(2) combination, whereas fibrosis and necrosis were nearly similar in both groups, In the 90-day groups, no inflammation was seen. No difference between the two 90-day groups with regard to reparative dentin was found.
Keywords: MONKEY PULPS; EXPOSURES